1983
DOI: 10.1128/aac.24.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antiviral activity of acyclovir and interferon on human cytomegalovirus

Abstract: The efficacy of human alpha interferon (IFN-a) combined with 9-(2'-hydroxyethoxymethyl)guanine (acyclovir; ACV), (E)-5-(2-bromovinyl)-2'-deoxyuridine, 9-0-D-arabinofuranosyladenine, or 1-0-D-arabinofuranosylcytosine on the inhibition of human cytomegalovirus (HCMV) replication in human embryonic lung cells was analyzed by plaque reduction assays. IFN-a combined with 9-,B-Darabinofuranosyladenine or 1-,B-D-arabinofuranosylcytosine produced an additive antiviral activity with respect to HCMV plaque formation. IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…DHPG-IFN-f synergism was observed over a very limited dose range, particularly in yield inhibition assays. This is also consistent with data obtained for IFN-a-acyclovir which showed that an increase in the concentration of the drug in the presence of a constant amount of IFN changed the inhibitory effects from additive to synergistic (25). The lack of synergy between IFN-a and DHPG in inhibiting CMV is in contrast to the findings for acyclovir, a structurally related compound (10,25,27).…”
contrasting
confidence: 56%
“…DHPG-IFN-f synergism was observed over a very limited dose range, particularly in yield inhibition assays. This is also consistent with data obtained for IFN-a-acyclovir which showed that an increase in the concentration of the drug in the presence of a constant amount of IFN changed the inhibitory effects from additive to synergistic (25). The lack of synergy between IFN-a and DHPG in inhibiting CMV is in contrast to the findings for acyclovir, a structurally related compound (10,25,27).…”
contrasting
confidence: 56%
“…It is thought that it may be related with the presence of HCMV genome in tumor cells (6,7). One of the medications which is effective on HCMV is acyclovir (ACV) (25)(26)(27). Acyclovir is a type of nucleoside analog and well tolerated, widely used antiviral drug (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…ara-A, acyclovir, hu man immunoglobulin, interferons and their combinations have shown enhanced antiviral effects [Cho et al, 1976;Feng, 1977, 1980;Strulovitch et al, 1979;Schinazi and Nahmias, 1982;Bryson and Kronenberg, 1977]. Similar studies have been reported with varicella-zoster and human cytomegalovirus [Smith et al, 1983]. However, no one has used acyclovir-vidarabine combination therapy against HSV2 infection in newborn mice.…”
Section: Introductionmentioning
confidence: 53%